OTTOMAN FIRMANS ADDRESSED TO KAITAG RULERS (PARIS COLLECTION) - Sadykov, Murad Gasretovic (History, Archeology and Ethnography of the Caucasus, 2022)
The paper presents a number of epistolary sources in the Ottoman language from the collection of firmans of Turkish sultans and viziers, addressed to Kaitag utsmeys. Microfilms of these firmans were obtained from the National Library of France, and their copies are now stored in the Collection of Oriental Manuscripts, in the Institute of History, Archeology and Ethnography of the DFRC RAS. The Utsmey collection most probably came to France in the second half of the 19th century. Some copies of the firmans are also stored in the archives of Georgia; partly they were published by Georgian researchers with transcription and translation into Georgian and Russian. Here we present translations and facsimiles of firmans of Turkish sultans, provided with appropriate comments, to the Dagestan rulers of the second half of the 18th – the first half of the 19th centuries, namely, the Kaitag utsmeys Ahmad Khan, Khamzat Khan, Ali Bek Khan and Adil Khan. The documents are of high scientific value and shed light on the policy of the Ottomans in the Caucasus, on the historical events associated with the liberation struggle of the Dagestan peoples, and on the foreign policy of the Dagestan rulers. Firmans convey the atmosphere of historical events, contain an assessment of the military and political achievements of the mountaineers by the Turkish rulers. At the same time, the studied sources inform that initially the Ottoman rulers promised the Dagestanis significant privileges in exchange for their obedience to the Ottoman Empire, however, later they began to call them to a holy struggle against foreign conquerors, for which they would receive “retribution from the Almighty”. Publication of the firmans may significantly enrich the source base on the socio-political history of the North Caucasus.
Keywords: Dagestan; firmans of Ottoman sultans; Kaitag Utsmyistvo; Nadir Shah; Russo-Turkish wars